2015
DOI: 10.1093/mnras/stv1328
|View full text |Cite
|
Sign up to set email alerts
|

Polarized radio filaments outside the Galactic plane

Abstract: We used data from the WMAP satellite at 23, 33 and 41 GHz to study the diffuse polarised emission over the entire sky. The emission originates mostly from filamentary structures with well-ordered magnetic fields. Some of these structures have been known for decades in radio continuum maps. Their origin is not clear and there are many filaments that are visible for the first time. We have identified and studied 11 filaments. The polarisation fraction of some of them can be as high as 40%, which is a signature o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
169
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(194 citation statements)
references
References 75 publications
17
169
1
Order By: Relevance
“…22 and 23). Most of the high-latitude polarized emission is associated with distinct large-scale loops and spurs, and we rediscuss their structure following the earlier study of Vidal et al (2015) based on WMAP observations. We argue that nearly all the emission at −90 • < l < 40 • is part of the Loop I structure, and show that the emission extends much further into the southern Galactic hemisphere than previously recognized, giving Loop I an ovoid rather than circular outline.…”
Section: Low Frequency Foregroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 and 23). Most of the high-latitude polarized emission is associated with distinct large-scale loops and spurs, and we rediscuss their structure following the earlier study of Vidal et al (2015) based on WMAP observations. We argue that nearly all the emission at −90 • < l < 40 • is part of the Loop I structure, and show that the emission extends much further into the southern Galactic hemisphere than previously recognized, giving Loop I an ovoid rather than circular outline.…”
Section: Low Frequency Foregroundsmentioning
confidence: 99%
“…Synchrotron polarization amplitude map, P = Q 2 + U 2 , at 30 GHz, smoothed to an angular resolution of 60 , produced by a weighted sum of Planck and WMAP data as described in Planck Collaboration XXV (2016). The traditional locii of radio loops I-IV are marked in black, a selection of the spurs identified by Vidal et al (2015) in blue, the outline of the Fermi bubbles in magenta, and features discussed for the first time in Planck Collaboration XXV (2016) in red. Our measured outline for Loop I departs substantially from the traditional small circle.…”
Section: The Galactic Magnetic Fieldmentioning
confidence: 99%
“…The synchrotron spectral index varies by only a few tenths across the sky, and to map it with useful precision we need a substantial gain in sensitivity. This has been achieved mainly by working at low resolution (Fuskeland et al 2014;Vidal et al 2015); in the current paper we use a fixed template for the synchrotron spectrum (Sect. 4.3 below).…”
Section: A First Look At the Low-frequency Foregrounds Using Constraimentioning
confidence: 99%
“…The main limitation in obtaining accurate components maps is the precise quantification of the synchrotron component. Fuskeland et al (2014) and Vidal et al (2015) have shown that the polarized spectral index of synchrotron emission varies across the sky and these variations should be taken into account to obtain an accurate separation between the synchrotron and AME components; low frequency (5-20 GHz) data will be crucial for this.…”
Section: Comparison With Wmap Modelsmentioning
confidence: 99%
See 1 more Smart Citation